Religion and Conservation: A Review of Use and Protection of Sacred Plants and Animals in Nepal (Journal of Institute of Science and Technology, 2015)
The objective of this paper is to examine the socio-cultural and spiritual values of plants and animals. It focuses on how religious beliefs and practices affect the way these species are understood, utilized and managed. Large number of plant and animal species with religious importance has been found to be conserved and protected in Nepal. Religious prospect has played a significant role in conservation of plants and animals.Journal of Institute of Science and Technology, 2015, 20(2): 61-66